The Difference in the Effects of Open Kinetic Chain Exercise and Isometric Exercise on the Quadriceps Muscles in Reducing Pain in Patients with Knee Osteoarthritists with Knee Osteoarthritis - Maryono, Maryono; Pajar Haryatno; Nitaya Putri (Poltekkes Kemenkes Surakarta, 2023)
Background: Knee osteoarthritis causes a decrease in quadriceps muscle strength and pain during activities. Strengthening the quadriceps muscles through exercise effectively reduces pain and improves the quality of life of patients. The purpose of this study was to compare the effects of open kinetic chain (OKC) and isometric exercises on pain reduction in patients with knee osteoarthritis. Methods: This study used a quasi-experimental two-group pre- and post-test design with 40 patients with knee osteoarthritis. Patients were randomly divided into two groups of 20 people. Group I performed OKC exercises and group II performed isometric exercises for 4 weeks (3 sessions/week). Pain was measured using the valid and reliable Visual Analog Scale (VAS). Data analysis used the Wilcoxon test for pre- and post-comparisons within each group and the Mann-Whitney test for differences between groups. Results: OKC and isometric exercises significantly reduced pain in patients. The mean VAS reduction in the OKC group was 2.10 ± 0.60, while in the isometric group it was 1.20 ± 0.51. The difference in pain reduction between groups was significant (p < 0.001). Conclusion: OKC exercise was more effective in reducing knee osteoarthritis pain than isometric exercise. It is recommended that OKC exercise be used as the primary intervention in knee osteoarthritis physiotherapy rehabilitation for optimal results. Further studies with larger samples and longer durations are needed.